StyleAI: A Comprehensive Framework for AI-Driven Personalized Fashion Recommendations in SaaS Retail Applications - Srikar Kompella, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive analysis of StyleAI, an innovative Software-as-a-Service (SaaS) platform that leverages artificial intelligence to revolutionize the online fashion retail experience. The article explores the core AI functionalities of StyleAI, including advanced image recognition, virtual try-on technology, and personalized recommendation systems. It delves into the complex engineering considerations required to build a scalable and robust SaaS platform, addressing challenges in microservices architecture, image processing, and e-commerce integration. The article also examines StyleAI's monetization strategies, discussing subscription models, commission-based revenue, and brand partnerships. Furthermore, it identifies current challenges and future directions for the platform, such as scalability concerns, AI model accuracy, user privacy, and integration with emerging technologies. By providing an in-depth look at the intersection of AI, fashion retail, and SaaS application development, this article offers valuable insights for researchers, developers, and industry professionals seeking to understand and implement AI-driven solutions in the rapidly evolving landscape of e-commerce and personalized retail experiences.
Keywords: AI-driven fashion recommendations; Virtual try-on technology; SaaS e-commerce platform; Personalized retail experience; Fashion image recognition